Effects of chronic sleep deprivation on upper respiratory tract mucosal histology and mucociliary clearance on rats. (8th May 2020) - Sazak Kundi, Fatma Cemre; Murat Ozcan, Kursat; Okudan, Berna; Coskun, Nazim; Inan, Mehmet Arda; Ozcan, Muge
Abstract: In this study, we aimed to investigate the effects of chronic sleep deprivation on mucociliary clearance, which is the primary defence mechanism of the upper airway tract and nasal mucosal histology. Forty‐two Wistar Albino rats (250‐300 g), 8 or 12 weeks old, were randomly assigned into three groups as follows. The first sleep‐deprivation group consisted of 14 rats (A), another 14 of them were assigned to platform group (B), and the remaining 14 were included to the home cage control group (C). For the two deprivation groups (A and B), the modified multiple platform method (MMPM) was used to induce sleep deprivation for 21 days. Tc‐99m MAA rhinoscintigraphy was performed to assess mucociliary clearance and the nasal histopathological changes of the sacrificed rats were also examined. Mucociliary clearance was significantly higher in sleep deprivation (A) and deprivation control (B) groups than the control group (C) ( p  = .037). The ratio of columnar ciliary was significantly higher in group A and B than in the control group ( p  = .003). The transitional epithelial ratio in groups A and B was also significantly increased compared with group C ( p  = .04). The control group's squamous epithelial ratio was increased compared to the sleep‐deprived groups ( p  = .003). There was a significantly increased inflammatory response in the ciliated columnar epithelium in groups A and B compared to group C ( p  = .02). For the first time in the literature, we demonstrated that chronic sleep deprivation has caused a significant increase in mucociliary clearance speed and in the number of ciliary cells.